2018
DOI: 10.5551/jat.42101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cilnidipine, an L/N-Type Calcium Channel Blocker, on Carotid Atherosclerosis in Japanese Post-Stroke Hypertensive Patients: Results from the CA-ATTEND Study

Abstract: Aims: Although several antihypertensive agents reduced the carotid intima-media thickness (IMT), it remains unclear whether those agents affect the interadventitial diameter (IAD). We aimed to examine whether cilnidipine, an L/N-type calcium channel blocker, reduced the common carotid IMT or IAD in post-stroke hypertensive patients.Methods: The common carotid IMT and IAD were measured at the start of cilnidipine treatment and 12 months from that. The changes in the mean max-IMT or IAD between baseline and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Carotid IMT was also considered as a surrogate clinical endpoint for several clinical trials using lipid-lowering, antihypertensive, and/or antidiabetic drugs 34 43 ) . A systematic review and meta-analysis showed that low density lipoprotein cholesterol reduction by a statin treatment and carotid IMT change reduction strongly correlated 44 ) .…”
Section: Carotid Imtmentioning
confidence: 99%
See 2 more Smart Citations
“…Carotid IMT was also considered as a surrogate clinical endpoint for several clinical trials using lipid-lowering, antihypertensive, and/or antidiabetic drugs 34 43 ) . A systematic review and meta-analysis showed that low density lipoprotein cholesterol reduction by a statin treatment and carotid IMT change reduction strongly correlated 44 ) .…”
Section: Carotid Imtmentioning
confidence: 99%
“…However, few studies exist on whether carotid IAD is more suitable screening point than carotid IMT for risk stratification of future cerebral or cardiovascular events. Carotid IAD might be decreased by several medications such as antihypertensive agents 43 ) . Although it also may be considered as a surrogate clinical endpoint using several medical intervention, few investigations to assess those associations exist.…”
Section: Other Aspects Of Assessments Using Carotid Ultrasonographmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, great care was taken to select the same level of the common carotid artery at baseline and at follow-up. Fourth, considering that several clinical studies have reported anti-atherosclerotic effects of ACE inhibitors, ARB, or CCB 33 , 34 ) , these medications should be considered as an adjusting covariate. Although chronic use of ACE inhibitors, ARB, or CCB without changes in the doses in our study could imply that their effects on carotid artery elasticity parameters might be less pronounced than new use or dosage change of these medications just before or during the study, their influence on carotid artery elasticity cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Many randomized clinical trials evaluated the effect of anti-hypertensive therapy on C-IMTp. Favorable effects were obtained with either diuretics [113], β-blockers [114][115][116][117], ACE inhibitors [44,118,119], angiotensin II receptor antagonists [116], calcium channel blockers [113][114][115]118,120] or α1 receptor -selective blockers [121]. Only a few studies with ACE inhibitors failed to detect significant effects.…”
Section: Control Of Hypertension and C-imtpmentioning
confidence: 99%